REPORT OF THE WSCUC VISITING TEAM ACCREDITATION REVIEW
CI was granted Initial Accreditation in 2007; the April 2015 review is its first for reaffirmation. The team carefully studied the institutional report and supporting documents in the fall of 2014. It met at WSCUC headquarters on October 29–30, 2014, to discuss its initial responses to the CI report and materials, conduct a video conference with the president and executive staff, and identify lines of inquiry for the visit. The team held a subsequent conference call on February 27, 2015 to prepare for the visit, conducted on April 7–10, 2015.